On the structural origin of free volume in 1-alkyl-3-methylimidazolium ionic liquid mixtures: a SAXS and 129Xe NMR study. - Weber,CC; Brooks,NJ; Castiglione,F; Mauri,M; Simonutti,R; Mele,A; Welton,T (Physical Chemistry Chemical Physics, 2019)
Ionic liquid (IL) mixtures enable the design of fluids with finely tuned structural and physicochemical properties for myriad applications. In order to rationally develop and design IL mixtures with the desired properties, a thorough understanding of the structural origins of their physicochemical properties and the thermodynamics of mixing needs to be developed. To elucidate the structural origins of the excess molar volume within IL mixtures containing ions with different alkyl chain lengths, 3 IL mixtures containing 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ILs have been explored in a joint small angle X-ray scattering (SAXS) and 129Xe NMR study. The apolar domains of the IL mixtures were shown to possess similar dimensions to the largest alkyl chain of the mixture with the size evolution determined by whether the shorter alkyl chain was able to interact with the apolar domain. 129Xe NMR results illustrated that the origin of excess molar volume in these mixtures was due to fluctuations within these apolar domains arising from alkyl chain mismatch, with the formation of a greater number of smaller voids within the IL structure. These results indicate that free volume effects for these types of mixtures can be predicted from simple considerations of IL structure and that the structural basis for the formation of excess molar volume in these mixtures is substantially different to IL mixtures formed of different types of ions.